Patient participatory behaviours in healthcare service delivery: Self-determination theory (SDT) perspective. Issue 2 (13th March 2017) - Osei-Frimpong, Kofi
Abstract : Purpose: The purpose of this paper is to deepen the understanding on patient participatory behaviours in co-creation of value drawing from the perspective of self-determination theory (SDT) focussing on motivation in particular. Design/methodology/approach: A model is proposed to suggest the influence of the various motivation types on a patient's participatory behaviours drawing from SDT. Following survey design approach, data collected from 345 outpatients from a quasi-government health facility in Accra, Ghana are examined through structural equation modelling using SmartPLS (v. 3.2.3). Findings: The findings reveal that patient participatory behaviours are influenced by both controlled and autonomous regulations leading to value attainment. External regulation (a more controlled form of extrinsic motivation) and patient participation in clinical encounters have no significant relationship with a patient's commitment to compliance with medical instructions. The results reveal patient compliance is largely driven by autonomous regulation as proposed by SDT. However, active patient participation in clinical encounters and commitment to compliance with medical instructions positively and significantly influences perceived value outcomes. Research limitations/implications: This research provides empirical evidence in support of understanding patient participatory behaviours in healthcare service delivery by testing theoretically grounded hypotheses developed from SDT perspective. The study focussed on outpatients from one quasi-government health facility, which could limit the generalisation of the findings reported. Practical implications: This study illustrates the need for service providers to understand participant's needs and motivation during the service encounter. This is essential as the various types of motivation influence the nature of the participation throughout the process, which could help improve on the value outcomes from the service. Originality/value: This study makes a significant contribution to service literature through the application of SDT to explain patient participatory behaviours in healthcare service delivery, production and value outcomes. From a theoretical perspective, the developed model integrates multiple research disciplines (e.g. SDT, participatory behaviours, and value co-creation) and extends research on patient integration, participation, and compliance.